BIOTECHNOLOGICAL PRODUCTION OF XANTHAN GUM IN SOME AGRO-INDUSTRIAL WASTE, CHARACTERIZATION AND APPLICATIONS - Menezes, Jeane Denise de Souza; Druzian, Janice Isabel; Padilha, Francine Ferreira; Souza, Roberto Rodrigues de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707165 The waste generated in the agribusiness represent economic losses in the production process andunless they receive proper destination, may provide environmental problems, highlighting theneed for installation of sustainable production systems. In this sense, the optimization ofbiotechnological processes for the production of xanthan gum from agro-industrial wasteproduction become more viable. Xanthan gum is a microbial heteropolysaccharide extracellularused as rheology control agent in aqueous systems and stabilizers in emulsions and suspensions.Because of these properties is widely used in a wide range of industries such as food,pharmaceuticals, toiletries, cosmetics, oil, among others. This paper aims to conduct a review onthe use of residual biomass in the production of xanthan gum, a survey of the major advances tominimize production of biopolymer and a review of the applicability of gum. The use of alternativesubstrates could help the production of xanthan gum in the country, helping to eliminate environmental problems such as effluent disposal, enabling economic recovery of this waste,besides that Brazil could meet its own demand of xanthan gum with greater competitiveness thefinal price.